Perovskite quantum dot surface in-situ polymer passivation method

By growing the polymer passivation layer in situ on the surface of perovskite quantum dots, the problem of unstable properties of perovskite quantum dots is solved, and the fluorescence stability improvement and good compatibility of polymer materials is achieved, and the improvement of fluorescence stability is achieved, which has expanded the Application prospects.

CN119463868APending Publication Date: 2025-02-18SOUTHWEAT UNIV OF SCI & TECH +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411492057.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Perovskite quantum dot materials are unstable in nature and are susceptible to factors such as heat, oxygen, and light, which weakens the fluorescence effect, and are sensitive to polar solvents, resulting in lattice phase change and defects, limiting its application in optoelectronic devices and other fields. .

Method used

By growing a polymer passivation layer in situ on the surface of perovskite quantum dots, organic polymer ligands are well compatible with polymer materials such as photocured resins and polystyrene, forming a dense crosslinked polymer layer to improve fluorescence stability.

Benefits of technology

The fluorescence stability of perovskite quantum dots has been improved, the ligand fallout problem has been avoided, the compatibility with polymer materials has been enhanced, and its application prospects in optoelectronic devices and other fields have been expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463868A_ABST
    Figure CN119463868A_ABST
Patent Text Reader

Abstract

The invention relates to a perovskite quantum dot surface in-situ polymer passivation method, which comprises the following steps: preheating a cesium precursor to at least 100 DEG C, quickly adding the cesium precursor into an iodine lead precursor or bromine lead precursor which is insulated at 120-170 DEG C, reacting for 30-300 seconds, quickly putting into an ice-water cold bath after the reaction is completed, cooling the reaction system to room temperature, and drying to obtain the perovskite quantum dot surface in-situ polymer passivation. The surface of the perovskite quantum dot is modified by a polymer layer; both the iodine lead precursor and the bromine lead precursor contain a monomer composition, and the monomer composition is composed of a polymer monomer, a crosslinking monomer and a functional monomer. The invention aims to obtain the perovskite quantum dot with stable fluorescence, and the perovskite quantum dot can have good compatibility with high polymer materials such as light-cured resin, polystyrene, polycarbonate and polyethylene glycol terephthalate by introducing an organic polymer ligand.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite quantum dot preparation, and in particular relates to a method for in-situ polymer passivation of the surface of perovskite quantum dots. Background Art

[0002] Perovskite quantum dots have the advantages of high photoluminescence quantum yield and narrow emission peak (about 20nm), which makes them have great application potential in optoelectronic devices, photocatalysis, biomarkers, fluorescence imaging and solar cells in recent years. However, the instability of perovskite material properties has always restricted its development. Perovskite quantum dots are easily affected by factors such as heat, oxygen, and light in the environment, which can easily cause phase changes in their crystal structure, resulting in a phenomenon of weakening and even quenching of the fluorescence effect. And as the ambient temperature increases, the surface ligands of perovskite quantum dots will fall off due to the thermal quenching effect, and their fluorescence intensity decreases with the increase of temperature. The ionic properties of perovskite quantum dots make them extremely sensitive to polar solvents. In a humid natural environment, a large number of defects are easily generated inside and on the surface of quantum dots, such as Schottky defects, Frenkel defects, and anti-substitution defects, which lead to phase changes and distortions in the lattice. These properties restrict the development and practical application of perovskite quantum dots, so solving the instability of the properties of perovskite quantum dots has become one of the research focuses of researchers in this field.

[0003] Up to now, small molecule organic ligands are one of the main methods to improve the fluorescence stability of perovskite. However, a dynamic equilibrium of proton exchange will occur between common organic long-chain ligands such as oleates and amines, making it easy for weakly bound ligands on the surface of quantum dots to lose ions, resulting in rapid detachment of ligands, and even causing phase changes in quantum dots during processing or purification, resulting in decreased fluorescence stability. Compounding perovskite quantum dots into molecular sieve materials with regular porous structures is also a method to improve the luminescence stability of perovskite quantum dots, such as the Chinese patent with publication number CN116752116A. However, the size of this composite quantum dot is generally above the micron level, and its compatibility with the polymer matrix is ​​poor, which limits its broader application prospects, and therefore needs to be improved. Summary of the invention

[0004] In order to solve the problems of weak stability of organic small molecule ligand passivation layer and large size of inorganic molecular sieve shell and poor compatibility with polymer matrix in most application scenarios, a method based on in-situ polymer passivation on the surface of perovskite quantum dots is proposed. The purpose is to obtain a fluorescent stable perovskite quantum dot, which can have good compatibility with polymer materials such as photocurable resin, polystyrene, polycarbonate and polyethylene terephthalate by introducing organic polymer ligands.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A method for in-situ polymer passivation of a perovskite quantum dot surface comprises the following steps:

[0007] Preheating the cesium precursor to at least 100°C, rapidly adding it to the iodine lead precursor or the bromine lead precursor kept at 120-170°C, reacting for 30-300 seconds, and rapidly placing it in an ice water cooling bath after the reaction is completed to cool the reaction system to room temperature, thereby obtaining perovskite quantum dots with a surface modified polymer layer;

[0008] The iodine lead precursor and the bromine lead precursor both contain a monomer composition, and the monomer composition consists of a polymer monomer, a cross-linking monomer and a functional monomer.

[0009] Furthermore, the preparation method of the iodine lead precursor includes the following steps:

[0010] 88 mg PbI2, 279 mg ZnI2, 5-500 mg polymer monomer, 5-500 mg cross-linking monomer and 1-100 mg functional monomer were weighed and added into a brown three-necked flask with N2 and a condenser, and mixed. Meanwhile, 2.1 mL oleylamine, 1.75 mL oleic acid and 5 mL 1-octadecene were added into the three-necked flask, and ultrasonic degassing was performed at room temperature for 20 min. The reaction system was then transferred to an oil bath, and the reaction was kept warm for 1-6 hours at a programmed temperature of 100-170°C.

[0011] Furthermore, the preparation method of the bromine lead precursor includes the following steps:

[0012] Weigh 88 mg PbBr2, 5-500 mg polymer monomer, 5-500 mg cross-linking monomer and 1-100 mg functional monomer, add into a brown three-necked flask with N2 and condenser, mix, add 2.1 mL oleylamine, 1.75 mL oleic acid and 5 mL 1-octadecene into the three-necked flask, and degas by ultrasonic at room temperature for 20 min. Then transfer the reaction system into an oil bath, and keep the reaction at 100-170°C for 1-6 hours.

[0013] Furthermore, the programmed temperature rise process of 100-170° C. in the preparation process of the iodine lead precursor or the bromine lead precursor includes sequentially keeping warm at 100° C. for 10-60 minutes, keeping warm at 120° C. for 10-300 minutes, keeping warm at 150° C. for 10-60 minutes and keeping warm at 170° C. for 10-30 minutes.

[0014] Furthermore, the polymer monomer is one or more of styrene, vinyl carbazole, methyl methacrylate, ethyl methacrylate, ethyl acrylate, acrylamide

[0015] Furthermore, the cross-linking monomer is one or more of divinylbenzene, ethylene glycol diacrylate, trimethylolpropane triacrylate, butadiene, and isoprene. The cross-linking monomer is copolymerized with the polymer monomer to expand the linear polymer grown in situ on the surface of the quantum dots into a three-dimensional network structure, and the prepolymer passivation layer structure is more compact and heat-resistant, thereby improving the fluorescence stability of the quantum dots by hindering the contact between the quantum dots and the external environment.

[0016] Furthermore, the functional monomer is one or more of maleic anhydride, vinyl trimethoxysilane, methacryloxypropyl trimethoxysilane, acrylonitrile, and vinyl toluene. By introducing the functional monomer, the wettability of the passivation polymer layer on the surface of the quantum dots is changed, on the one hand, the compatibility of the quantum dots with the target matrix is ​​improved, and on the other hand, the contact between the quantum dots and the surrounding environment is selectively isolated.

[0017] Beneficial effects of the present invention:

[0018] (1) The present invention proposes to grow a prepolymer in situ on the surface of a perovskite quantum dot precursor (lead iodide or lead bromide precursor) to obtain a lead iodide or lead bromide precursor wrapped by the prepolymer. The cesium precursor is injected into the lead iodide or lead bromide precursor wrapped by the above-prepared prepolymer by a hot injection method to obtain a quantum dot solution. The reaction temperature and reaction time are studied to ensure that the two precursors can pass through the prepolymer layer and react fully. This preparation scheme can replace the organic small molecule ligand passivation layer in the prior art, avoid the problem of ligand shedding, and convert the prepolymer into a polymer in situ, or even a cross-linked polymer, during the reaction of the precursor into a perovskite quantum dot, thereby improving the fluorescence stability of the perovskite quantum dot.

[0019] At the same time, since the external wrapping of perovskite quantum dots is a polymer material, it replaces the inorganic porous material molecular sieve in the prior art, and has good compatibility with polymer materials such as photocurable resins, polystyrene, polycarbonate and polyethylene terephthalate, and can be evenly dispersed in the polymer matrix.

[0020] (2) The present invention introduces a monomer composition (polymerization monomer, cross-linking monomer and functional monomer) during the precursor synthesis stage and induces prepolymerization, which can prevent the polymerization reaction conditions from affecting the fluorescence stability of perovskite quantum dots. The molecular weight, compactness and functionality of the prepolymer can be controlled by regulating the ratio between the precursor and the monomer, the ratio between the cross-linking monomer and the polymerization monomer, the amount and type of the functional monomer introduced, the reaction temperature and the reaction time. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 TEM image of polystyrene modified CsPbI3 QDs prepared in Example 1;

[0022] Figure 2 FTIR image of polystyrene modified CsPbI3 QDs prepared in Example 1;

[0023] Figure 3 The absorption and emission spectra (PL) of the products prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0024] In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific implementation methods described here are only used to explain the present invention and are not used to limit the present invention.

[0025] Embodiment 1:

[0026] A method for in-situ polymer passivation of a perovskite quantum dot surface comprises the following steps:

[0027] Cesium precursor: Weigh 100 mg of Cs2CO3, 0.4 mL of oleic acid (OA), and 3.5 mL of 1-octadecene (ODE), add the mixture to a brown three-necked flask filled with N2, degas and keep warm at 80°C for 30 min, then raise the temperature to 120°C and stir and keep warm for 30 min. When Cs2CO3 is completely dissolved into a light yellow clear liquid, cool the reaction system naturally to room temperature and store it away from light.

[0028] Iodine lead precursor: 88 mg PbI2, 279 mg ZnI2, 176 mg styrene, 88 mg divinylbenzene and 20 mg vinyltrimethoxysilane were weighed and added to a brown three-necked flask with N2 and a condenser, and 2.1 mL oleylamine, 1.75 mL oleic acid and 5 mL 1-octadecene were added. Ultrasonic degassing was performed for 20 min at room temperature. The reaction system was then transferred to an oil bath and kept warm for 4 hours during a programmed temperature rise of 100 to 170 ° C (the programmed temperature rise of 100 to 170 ° C includes keeping warm at 100 ° C for 0.5 h, 120 ° C / 2.5 h, 150 ° C / 0.5 h, and 170 ° C / 0.5 h in sequence).

[0029] The cesium precursor prepared in advance was preheated to 100°C, 0.4 mL of the cesium precursor was taken out and quickly added to the iodine-lead precursor kept at 120-170°C, reacted for 120 seconds, and then quickly placed in an ice water cold bath to cool the system to room temperature to obtain perovskite quantum dots (CsPbI3 / PS) with a surface modified polymer layer.

[0030] In the above, the quantum dot hot injection reaction time: the iodine lead precursor is kept warm during the programmed temperature rise process = 2 minutes (120 seconds): 240 minutes.

[0031] Post-treatment purification: 8 mL of toluene was added to the product system of the perovskite quantum dots with a surface modified polymer layer, and the mixture was centrifuged at 3000 rpm for 3 minutes to obtain the supernatant; 40 mL of methyl acetate was then added to the supernatant, and the mixture was centrifuged at 9000 rpm for 5 minutes to remove the supernatant to obtain a precipitate containing the quantum dot product; finally, the precipitate was dissolved in 4 mL of n-octane and centrifuged at 3000 rpm for 3 minutes at room temperature, and the supernatant was filtered with a 0.22 μm PTFE membrane to obtain a pure n-octane solution of the perovskite quantum dots with a surface modified polymer layer.

[0032] Experimental results: Figure 1 It can be seen that the size distribution of the polystyrene-modified perovskite quantum dots (CsPbI3 / PS) prepared in this example is uniform, and the average size of the polystyrene-modified CsPbI3 QDs is about 8nm. It can be observed that a thin layer of polystyrene is attached to the crystal surface. Figure 2 The FTIR spectrum shown also shows the characteristic peaks of polystyrene, indicating the successful synthesis of CsPbI3 / PS.

[0033] Comparative Example 1:

[0034] The difference from Example 1 is that no polymer monomer, cross-linking monomer and functional monomer are added to the iodine lead precursor, so that the synthesized quantum dot CsPbI3 does not have a surface modified polymer layer.

[0035] like Figure 3 As shown, the emission peak of CsPbI3 prepared in this comparative example 1 is 628nm, while the emission peak of CsPbI3 / PS prepared in Example 1 is 660nm. After the preparation scheme of the present application, the emission wavelength of the quantum dots undergoes a red shift phenomenon and the red shift is about 32nm.

[0036] Comparative Example 2:

[0037] The difference from Example 1 is that the reaction time of the hot injection stage is adjusted, that is, the cesium precursor is controlled to pass through the prepolymer layer and fully react with the iodine lead precursor. That is, the quantum dot hot injection reaction time: the iodine lead precursor is kept warm during the program temperature rise process = 1 minute (60 seconds): 240 minutes.

[0038] Specifically:

[0039] The cesium precursor prepared in advance was preheated to 100°C, 0.4 mL of the cesium precursor was taken out and quickly added to the iodine-lead precursor kept at 120-170°C, reacted for 60 seconds, and then quickly placed in an ice water cold bath to cool the system to room temperature to obtain perovskite quantum dots (CsPbI3 / PS) with a surface modified polymer layer.

[0040] Comparative Example 3:

[0041] The difference from Example 1 is that the degree of the lead iodide precursor wrapped by the prepolymer layer is regulated, so as to control the cesium precursor to pass through the prepolymer layer and fully react with the lead iodide precursor. That is, the quantum dot hot injection reaction time: the lead iodine precursor is kept warm during the programmed temperature rise process = 2 minutes (120 seconds): 120 minutes.

[0042] Specifically:

[0043] Lead iodine precursor: Weigh 88 mg PbI2, 279 mg ZnI2, 176 mg styrene, 88 mg divinylbenzene and 20 mg vinyltrimethoxysilane and add them to a brown three-necked flask with N2 and a condenser, and add 2.1 mL oleylamine, 1.75 mL oleic acid and 5 mL 1-octadecene. Ultrasonic degassing for 20 minutes at room temperature. The reaction system was then transferred to an oil bath and kept warm for 2 hours during a programmed temperature rise of 100 to 170 ° C (the programmed temperature rise process of 100 to 170 ° C includes keeping warm at 100 ° C for 0.25 h, 120 ° C / 1.25 h, 150 ° C / 0.25 h, 170 ° C / 0.25 h in sequence)

[0044] The present invention measures the fluorescence quantum yield and stability test of the products of Example 1 and Comparative Examples 1-3 respectively. Among them, the fluorescence quantum yield test method is a prior art and will not be repeated here. Fluorescence stability test method of perovskite quantum dots in water: take about 0.2mL of n-octane solution of perovskite quantum dots, add 1mL of tap water thereto, and stir for 1min to make the quantum dots fully contact with tap water. Observe the fluorescence decay under ultraviolet light, and record the time when the fluorescence is completely quenched. Repeat the test for 3 groups and record them in Table 1.

[0045] The test results are shown in Table 1 below:

[0046] Example / Comparative Example Fluorescence quantum yield (PLQY) Fluorescence stability test results Example 1 75.94% >48h Comparative Example 1 47.25% 1.5~2.0h Comparative Example 2 51.25% 30~32h Comparative Example 3 67.53% 44~48h

[0047] Table 1

[0048] The present invention illustrates the detailed preparation method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed preparation method, that is, it does not mean that the present invention must rely on the above-mentioned products and detailed preparation methods to be implemented. It should be clear to those skilled in the art that any improvement of the present invention, the combination or equivalent replacement of the raw materials of the product of the present invention, all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for in-situ polymer passivation of the surface of perovskite quantum dots, characterized in that: The steps include: Preheating the cesium precursor to at least 100°C, rapidly adding it to the iodine lead precursor or the bromine lead precursor kept at 120-170°C, reacting for 30-300 seconds, and rapidly placing it in an ice water cooling bath after the reaction is completed to cool the reaction system to room temperature, thereby obtaining perovskite quantum dots with a surface modified polymer layer; The iodine lead precursor and the bromine lead precursor both contain a monomer composition, and the monomer composition consists of a polymer monomer, a cross-linking monomer and a functional monomer.

2. The method for in-situ polymer passivation of the surface of perovskite quantum dots according to claim 1, characterized in that: The preparation method of the cesium precursor comprises the following steps: Weigh 100 mg of Cs2CO3, 0.4 mL of oleic acid (OA) and 3.5 mL of 1-octadecene (ODE), mix and add into a brown three-necked flask with N2, degas and keep warm at 80°C for 30 min, then increase the temperature to 120°C and stir and keep warm for 30 min; when Cs2CO3 is completely dissolved into a light yellow clear and transparent liquid, the reaction system is naturally cooled to room temperature.

3. The method for in-situ polymer passivation of the surface of perovskite quantum dots according to claim 2, characterized in that: The preparation method of the iodine lead precursor comprises the following steps: Weigh 88 mg PbI2, 279 mg ZnI2, 5-500 mg polymer monomer, 5-500 mg cross-linking monomer and 1-100 mg functional monomer, add into a brown three-necked flask with N2 and condenser, mix, add 2.1 mL oleylamine, 1.75 mL oleic acid and 5 mL 1-octadecene into the three-necked flask, and degas by ultrasonic at room temperature for 20 min; then transfer the reaction system to an oil bath, and keep the reaction at 100-170°C for 1-6 hours.

4. The method for in-situ polymer passivation of the surface of perovskite quantum dots according to claim 1, characterized in that: The preparation method of the bromine lead precursor comprises the following steps: Weigh 88 mg PbBr2, 5-500 mg polymer monomer, 5-500 mg cross-linking monomer and 1-100 mg functional monomer, add into a brown three-necked flask with N2 and condenser, mix, add 2.1 mL oleylamine, 1.75 mL oleic acid and 5 mL 1-octadecene into the three-necked flask, and degas by ultrasonic at room temperature for 20 min. Then transfer the reaction system into an oil bath, and keep the reaction at 100-170°C for 1-6 hours.

5. The method for in-situ polymer passivation of the surface of perovskite quantum dots according to claim 4, characterized in that: Post-processing steps are also included: Add 8 mL of toluene to the product of the perovskite quantum dots of the surface modified polymer layer, centrifuge at 3000 rpm for 3 minutes, and take the supernatant; then add 40 mL of methyl acetate to the supernatant, centrifuge at 9000 rpm for 5 minutes, remove the supernatant, and obtain a precipitate containing the quantum dot product; Finally, the precipitate was dissolved in 4 mL of n-octane and centrifuged at 3000 rpm for 3 minutes at room temperature. The supernatant was filtered through a 0.22 μm PTFE membrane to obtain an n-octane solution of pure perovskite quantum dots with a surface-modified polymer layer.

6. The method for in-situ polymer passivation of the surface of perovskite quantum dots according to claim 1, characterized in that: The programmed temperature rise process of 100-170° C. in the preparation process of the iodine lead precursor or the bromine lead precursor comprises sequentially keeping warm at 100° C. for 10-60 minutes, keeping warm at 120° C. for 10-300 minutes, keeping warm at 150° C. for 10-60 minutes and keeping warm at 170° C. for 10-30 minutes.

7. The method for in-situ polymer passivation of the surface of perovskite quantum dots according to claim 1, characterized in that: The polymer monomer is one or more of styrene, vinyl carbazole, methyl methacrylate, ethyl methacrylate, ethyl acrylate, and acrylamide.

8. The method for in-situ polymer passivation of the surface of perovskite quantum dots according to claim 7, characterized in that: The cross-linking monomer is one or more of divinylbenzene, ethylene glycol diacrylate, trimethylolpropane triacrylate, butadiene, and isoprene.

9. The method for in-situ polymer passivation of the surface of perovskite quantum dots according to claim 8, characterized in that: The functional monomer is one or more of maleic anhydride, vinyl trimethoxy silane, methacryloxypropyl trimethoxy silane, acrylonitrile and vinyl toluene.

Citation Information

Patent Citations

  • Method for growing halide perovskite nanocrystals through in-situ chemical vapor deposition

    CN116752116A